A Sitrep About The Teachers’ Life Carrier Model From Bottom-, Plan- and Sideviews - Pete, József (Autonomy and Responsibility Journal of Educational Sciences, 2022)
My aim is to depict the operation of the system, the changing role of the infl uencing factors and the possible perspectives based on my experiences on the constantly modifi ed teachers’ lifecarrier model. So my presentation is a sitrep based on fact and experiences by which the following statements can be sketched. 1. Positive – the acceptance of the principles. The acknowledgement of the fi nancial incentives. The need for the measurement, the assessment and the support of the teachers’ work is generally accepted among the teachers. 2. Negative – some changes are inevitable. The increase of the awareness of the teachers. The transparency and consistency of system regulation. The keeping in mind of the needs of the teachers. The esteem of the experienced colleagues. Contact between the OH and the experts. Humanization of the system, bringing it closer to life and school. The harmonization of demands, values and performances - the increase of the validity and reliability of the qualifi cation, etc. 3. The reasons behind the problems. The results of fi nancing the project. The confl ict between the offi ce’s and the schools’ views. Not suffi ciently grounded introduction of the system.